Detection of fetal fibronectin in twin pregnancies in relation to gestational age - Oliveira, Tenilson Amaral; Carvalho, Carla Muniz Pinto de; Souza, Eduardo de; Mariani-Neto, Corintio; Camano, Luiz (São Paulo Medical Journal, 1999)
CONTEXT: The presence of fetal fibronectin in the cervix or vagina has been investigated as a possible marker for the risk of preterm birth. Fetal fibronectin in cervical fluid can provide direct evidence of pathologic changes at the interface of fetal and maternal tissues. OBJECTIVE: To evaluate the presence of fetal fibronectin as a predictor of premature delivery in twin pregnancies in relation to gestational age. DESIGN: Acuracy study. SETTING: University referral unit. PARTICIPANTS: 52 pregnant women with twin pregnancies and gestational age of between 24 and 34 weeks. MAIN MEASUREMENTS: Sensivity, specifity, predictive values and relative risk ratios of the correlation between fetal fibronectin and preterm birth before 34 and 37 weeks using an immediate-reading membrane test on cervicovaginal secretions obtained from participants. RESULT: The sensitivity varied between 66.7% and 85.7%, whereas the specificity was from 58.3% to 81.8% according to gestational age at the time of sampling. The relative risk of spontaneous preterm birth after a positive fetal fibronectin test, as compared with a negative fetal fibronectin test, rose from 2.8 at 24-26 weeks to 4.1 at 27-30 weeks. Analyses of the risk of delivery before 34 weeks were not statistically significant. CONCLUSION: Fetal fibronectin in the cervicovaginal secretions of patients with twin pregnancies is a useful tool for the early identification of twin pregnancies likely to deliver before 37 weeks. However, the clinical value of the fibronectin test is limited because of low indices for prediction of delivery before 34 weeks. The best period for performing the fetal fibronectin test in twin pregnancies to predict preterm delivery is between 27 and 30 weeks.